Consumer responses to savings message framing. (September 2020) - Yang, Bi; Mattila, Anna S.
Abstract: Despite the prevalent use of savings messages (e.g., "get $x off" and "save $x"), no previous tourism and hospitality research has examined their effect on consumer responses. To fill that void, this study investigates the joint effect of savings message type (gain-framed vs. nonloss-framed) and weather conditions (sunny vs. rainy) on consumer attitude. The results show that individuals in rainy weather respond more favorably to a gain-framed (vs. nonloss-framed) message, and this effect is attenuated among people in sunny weather. Furthermore, this study reveals a boundary condition. When the amount of savings is presented in percentage terms (e.g., "get x% off" and "save x%"), the superiority of a gain frame disappears. Theoretical and managerial implications are discussed. Highlights: Weather impacts the efficacy of gain-framed and nonloss-framed savings messages. A "get $x off" (vs. "save $x") message is more effective in rainy weather. The two savings messages are equally effective in sunny weather. A "get % off" message is not superior to a "save %" cue in rainy weather.